Direct-acting antiviral agent efficacy and safety in renal transplant recipients with chronic hepatitis C virus infection: A PRISMA-compliant study. Issue 30 (July 2017) - Chen, Keliang; Lu, Pei; Song, Rijin; Zhang, Jiexiu; Tao, Rongzhen; Wang, Zijie; Zhang, Wei; Gu, Min
Abstract: Background: The efficacy and safety of direct-acting antivirals (DAAs) for treating hepatitis C virus (HCV)-infected renal transplant recipients (RTRs) has not been determined. Methods: We searched PubMed, Embase, and the Cochrane Central Register of Controlled Trials and assessed the quality of eligible studies using the Joanna Briggs Institute scale. DAA efficacy and safety were assessed using standard mean difference (SMD) with 95% confidence intervals (95%CIs). Results: Six studies (360 RTRs) were included. Two hundred thirty six RTRs (98.3%) achieved sustained virological response within 12 weeks; HCV infection was cleared in 239 RTRs after 24-week treatment. Liver function differed significantly pre- and posttreatment (alanine aminotransferase, SMD: 0.96, 95%CIs: 0.65, 1.26; aspartate aminotransferase, SMD: 0.89, 95%CIs: 0.60, 1.18); allograft function pre- and posttreatment was not statistically different (serum creatinine, SMD: −0.13, 95%CIs: −0.38, 0.12; estimated glomerular filtration rate, SMD: 0.20, 95%CIs: −0.11, 0.51). General symptoms (fatigue nausea dizziness or headache) were the most common adverse events (AEs) (39.3%). Severe AEs, that is, anemia, portal vein thrombosis, and streptococcus bacteraemia and pneumonia, were present in 1.1%, 0.6%, and 1.1% of RTRs, respectively. Conclusion: Our findings suggest that DAAs are highly efficacious and safe for treating HCV-infected RTRs and without significant AE.